How conversational implicature can account for ordinary human conversational interaction / Kamisah Ariffin - Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2000)
Successful communication hinges on the hearer's grasping more than what is said by the speaker. The hearer normally relies on the presumption that the speaker is speaking truthfully, informatively, relevantly and appropriately in manner to make an inference from the utterance. However, what a speaker implicates may be different from what s/he says and from what his/her words imply. This article looks at how the conversational implicature can account for ordinary human conversational interaction.